2020
DOI: 10.3758/s13423-020-01814-8
|View full text |Cite
|
Sign up to set email alerts
|

The truth revisited: Bayesian analysis of individual differences in the truth effect

Abstract: The repetition-induced truth effect refers to a phenomenon where people rate repeated statements as more likely true than novel statements. In this paper, we document qualitative individual differences in the effect. While the overwhelming majority of participants display the usual positive truth effect, a minority are the opposite—they reliably discount the validity of repeated statements, what we refer to as negative truth effect. We examine eight truth-effect data sets where individual-level data are curate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…This is a bias of sorts, and it probably is used on statements where the participant is guessing about the truth of the statement. Schnuerch et al (2020) found that wherever individual differences were resolvable the unconstrained model outperformed the positive model. Their conclusion was that while most people had a true truth effect, a minority had the opposite.…”
Section: Biasesmentioning
confidence: 98%
See 2 more Smart Citations
“…This is a bias of sorts, and it probably is used on statements where the participant is guessing about the truth of the statement. Schnuerch et al (2020) found that wherever individual differences were resolvable the unconstrained model outperformed the positive model. Their conclusion was that while most people had a true truth effect, a minority had the opposite.…”
Section: Biasesmentioning
confidence: 98%
“…Here is a less obvious example. Schnuerch, Nadarevic, & Rouder (2020) examined individual differences in the truth effect with the methods outlined here. The truth effect occurs when people rate statements as more likely to be true when they are repeated.…”
Section: Biasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this classification we calculated the percentage of individuals who showed a "positive", a "negative" or no (undecided) distance effect. The benchmark for choosing a positive/negative classification was based on a similar classification by Schnuerch et al (2020). Please note that a posterior probability of 0.75 equates to an odds ratio of 3-to-1, which is considered a minimum threshold of evidence in Bayesian model comparison.…”
Section: Testing the Model Fit Of The Distributional Properties Of The Distance Effectsmentioning
confidence: 99%
“…The best model fit is then tested using a Bayes factor model comparison. This novel approach has been successfully implemented to test the structure of individual differences in numerical priming effects (Haaf and Rouder, 2019), location and color Stroop effects (Haaf and Rouder, 2019), numerical size congruity effects (Faulkenberry and Bowman, 2020), and the truth effect (Schnuerch et al, 2020).…”
Section: Introductionmentioning
confidence: 99%